2018
DOI: 10.1017/s2040174418000600
|View full text |Cite
|
Sign up to set email alerts
|

In vivoandin vitrobisphenol A exposure effects on adiposity

Abstract: In utero exposure to the ubiquitous plasticizer, bisphenol A (BPA) is associated with offspring obesity. As adipogenesis is a critical factor contributing to obesity, we determined the effects of in vivo maternal BPA and in vitro BPA exposure on newborn adipose tissue at the stem-cell level. For in vivo studies, female rats received BPA before and during pregnancy and lactation via drinking water, and offspring were studied for measures of adiposity signals. For in vitro BPA exposure, primary pre-adipocyte cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 92 publications
(133 reference statements)
2
51
0
Order By: Relevance
“…However, when these pups are exposed to NPD or to an overnutrition occur a greater ability to efficiently store nutrients that results in obesity later in life . Thus, the findings associated to the increase in the fad pad content observed in the mammary gland from LPD + BPA animals by histology analysis can be due to a compensatory response to IGR associated with postnatal BPA exposure, since BPA have been shown to activate PPAR‐gamma and induce adipogenesis …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, when these pups are exposed to NPD or to an overnutrition occur a greater ability to efficiently store nutrients that results in obesity later in life . Thus, the findings associated to the increase in the fad pad content observed in the mammary gland from LPD + BPA animals by histology analysis can be due to a compensatory response to IGR associated with postnatal BPA exposure, since BPA have been shown to activate PPAR‐gamma and induce adipogenesis …”
Section: Discussionmentioning
confidence: 99%
“…[40][41][42] Thus, the findings associated to the increase in the fad pad content observed in the mammary gland from LPD + BPA animals by histology analysis can be due to a compensatory response to IGR associated with postnatal BPA exposure, since BPA have been shown to activate PPAR-gamma and induce adipogenesis. 43,44 Estrogen and progesterone are major steroid hormones associated with cell proliferation and death and cellular differentiation in normal mammary gland. 31 In special, progesterone hormone particularly regulates tertiary side branching of epithelial ducts following ductal morphogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, adipocyte hypertrophy occurred in the progeny of rats that received BPA during pregnancy, along with a rise in the expression of pro-adipogenic factors. Proliferation of pre-adipocyte induced by BPA has been described in vitro as well [109,110,130]. In cultures of 3T3-L1 pre-adipocytes, the expression of PPARγ was enhanced by BPA, and lipid content in mature cells increased.…”
Section: Impact On Offspring: Short-term and Long-term Outcomesmentioning
confidence: 95%
“…A recent study by Desai et al (42), reported significant increases in BW and fat mass at 3 and 24 weeks of age in male but not female Sprague Dawley rats born to mothers exposed to BPA in their drinking water from 2 weeks prior to mating through pregnancy and lactation (5 mg BPA/liter which provided 500–900 μg/kg BW/day during pregnancy and ~1500 μg/kg BW/day during lactation). Further study of the BPA exposed males at 3 weeks of age revealed an increase in adipocyte size, lipogenic factors (SrebP1 and C/EBP alpha), and inflammation in the retroperitoneal fat pad.…”
Section: Factors That Can Influence Effects Of Bpa Exposure On Body Wmentioning
confidence: 99%